DESKRIPSI KEMAMPUAN PENALARAN MATEMATIS SISWA SMP KELAS VIII - Veronika Oktaviana; Indrie Noor Aini (IKIP Siliwangi, 2021)
The research carried out aims to describe the mathematical reasoning abilities of junior high school students. The approach used in this research is a descriptive qualitative approach. This research carried out using subjects from class VIII H students at one of SMP Negeri Karawang Timur with a total of 39 students. The instrument in this study uses questions of mathematical reasoning skills with 4 quadrilateral subjects in the form of descriptions. The data collection technique in this research carried out by giving 4 questions of mathematical reasoning ability test in the form of descriptions. The data analysis technique used in the research carried out applied the research of Miles and Huberman consisting of data reduction, data presentation, and conclusion drawing. Based on the explanation of the results and discussion namely 6 students with high mathematical reasoning abilities, 27 students with moderate mathematical reasoning abilities, and 6 students with low mathematical reasoning abilities, it was concluded that the mathematical reasoning abilities of junior high school students class VIII H at the school were in solving quadrilateral problems included in the medium category.